PELAKSANAAN PENGAWASAN IZIN MENDIRIKAN BANGUNAN OLEH DINAS CIPTA KARYA DAN TATA RUANG DI KABUPATEN SIAK - Bambang Supriadi; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Nowdays, there are too many people who still do not understand about theimportance of permission to construct a building. In addition, people still have aproblem on how to obtain a permit to erect a building as well as the provisions thatrestrict or regulate the establishment of a building in an area. Therefore, the needfor monitoring to see how the implementation has been done in the field as well asthe right to construct the building according to applicable regulations.The purpose of this study is to see how the implementation of surveillanceconducted by piupiupiu and to find out which one is the dominant factor in this study.This research was conducted in Dinas Cipta Karya dan Tata Ruang in Siak district.In conducting the data collection method using observation and in-depth interviewsto research informants. Once the data is collected and then drawn conclusions basedon the laws of inference and analyzed using qualitative descriptive analysis.After a study found that the factors that affect the implementation of thebuilding permit supervision by Dinas Cipta Karya dan Tata Ruang is the factor ofhuman resources, funding or budget, facilities and infrastructure, as well asdiscipline in applying the rules correctly.Keywords: Supervision, building permits, Spatial and Urban Planning